2012
DOI: 10.1152/ajpendo.00489.2011
|View full text |Cite
|
Sign up to set email alerts
|

Impaired β-cell-β-cell coupling mediated by Cx36 gap junctions in prediabetic mice

Abstract: Gap junctional intercellular communication between ␤-cells is crucial for proper insulin biosynthesis and secretion. The aim of this work was to investigate the expression of connexin (Cx)36 at the protein level as well as the function and structure of gap junctions (GJ) made by this protein in the endocrine pancreas of prediabetic mice. C57BL/6 mice were fed a high-fat (HF) or regular chow diet for 60 days. HF-fed mice became obese and prediabetic, as shown by peripheral insulin resistance, moderate hyperglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 40 publications
12
64
0
Order By: Relevance
“…6,86 The strength of this coupling decreases with age 87,88 and in animal models of diabetes. 89,90 Therefore, our simulations predict that a reduction in GJ coupling would reduce the ability of hubs to generate whole-islet Ca 2+ oscillations, greatly impairing insulin output. Whether such dysfunctions in hub cells occur in T2DM and contribute to the impaired insulin secretion observed in this disease, remains to be seen.…”
Section: Discussionmentioning
confidence: 90%
“…6,86 The strength of this coupling decreases with age 87,88 and in animal models of diabetes. 89,90 Therefore, our simulations predict that a reduction in GJ coupling would reduce the ability of hubs to generate whole-islet Ca 2+ oscillations, greatly impairing insulin output. Whether such dysfunctions in hub cells occur in T2DM and contribute to the impaired insulin secretion observed in this disease, remains to be seen.…”
Section: Discussionmentioning
confidence: 90%
“…These procedures were performed as previously described 19,40,41 and at the same period during the day (9 a.m.-11 a.m.). The blood glucose concentration was measured using an Accu-Chek Advantage II glucometer (Roche Diagnostic, Switzerland).…”
Section: Weight Gain and Metabolic Evaluationmentioning
confidence: 99%
“…20,41 Briefly, homogenate aliquots (containing 50 mg of total protein) were applied on 12% polyacrylamide gels and proteins were fractionated by electrophoresis and electrophoretically transferred to nitrocellulose membranes (Bio-Rad). After staining with Ponceau solution (Sigma) to check the efficiency of sample loading and transfer, membranes were blocked for 4 h at RT with a buffer solution (0.01 M Trisma Base, 0.15 M NaCl, 0.05% Tween 20; pH 7.4) containing 5% skimmed milk powder and then incubated overnight at 4 C with primary antibody anti-claudin-1 (Abcam; cat number ab15098; dilution 1:150 in basal solution containing 3% skimmed milk powder).…”
mentioning
confidence: 99%
“…Implications for Altered Gap Junction Coupling in DiabetesRecent studies have indicated that Cx36 gap junction coupling is decreased in islets from high-fat diet fed mouse models of pre-diabetes (24). [Ca 2ϩ ] i dynamics are also disrupted in an ob/ob mouse model of obesity (63) consistent with a decrease in gap junction coupling (18).…”
Section: Low Levels Of Pro-inflammatory Cytokines Disrupt [Ca 2ϩ ] I mentioning
confidence: 99%
“…This suggests that disruptions to gap junction coupling occur under these pre-diabetic and diabetic conditions. Recent studies have shown that Cx36 gap junction coupling is decreased in high-fat diet fed mice (24), which suggests a role for altered coupling in the development of disease. Furthermore, in vitro studies have shown that hyperglycemia (25) and hyperlipidemia (26,27), conditions that stimulate high levels of cytokine production from ␤-cells (28,29), reduce Cx36 gap junction coupling.…”
mentioning
confidence: 99%